2013
DOI: 10.4236/ojog.2013.37101
|View full text |Cite
|
Sign up to set email alerts
|

Canadian university students’ perceptions of future personal infertility

Abstract: Objective: University is a time for self-discovery, development of independence and transition to adulthood. It is not well examined whether childless university students also consider the potential of future personal infertility. The objective of this study was to document expectations and perceptions related to personal infertility in a sample of young adults. Methods: Using a qualitative approach, interviews were conducted with 39 male and female university students in Ottawa, Canada. Interview topics inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 63 publications
0
8
0
2
Order By: Relevance
“…In this study, 5 students expressed concerns about their inability to have children because of medical problems (such as menstrual irregularities or PCOS); this was also the case with students in a Canadian study. 27 However, a large majority of students in the present study stated that they started thinking about these issues after their course. Aysel …”
Section: Discussionmentioning
confidence: 59%
See 3 more Smart Citations
“…In this study, 5 students expressed concerns about their inability to have children because of medical problems (such as menstrual irregularities or PCOS); this was also the case with students in a Canadian study. 27 However, a large majority of students in the present study stated that they started thinking about these issues after their course. Aysel …”
Section: Discussionmentioning
confidence: 59%
“…40 In the focus group discussions, students recognized the huge emotional impact of this subject. In a previous study with a similar sample, 27 the authors suggested that not being able to have biological children may cause negative emotional reactions in participants.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Időszerű és releváns lenne tehát felmérni a meddőség érzelmi és testi következményei-ről alkotott elképzeléseket szakemberek, illetve jövőbeli szakemberek körében, mivel ez mindeddig csak laikusok körében valósult meg [11,18]. A testi tünetek ész-lelésének pontossága ugyanis elengedhetetlen a kezelés eredményességének szempontjából, az érzelmi terhek megértését pedig igénylik a páciensek [10].…”
unclassified